(untitled) (Comillas Journal of International Relations, 2019)
Uruguay has historically been singled out for its high democratic stability despite being located in such a volatile region such as Latin America. The attachment to the institutions, the political culture of its population, the continuity of its political parties, the social and political integration or the progress of its reforms have allocated the Uruguayan democracy as the oldest and most consolidated democracy in Latin America. Which are the circumstances that condition and promote governability in Uruguay? Which role do the political parties play in the construction of governability? Throughout an analysis of two different government experiences, this study aims to determine which are the factors that have historically enabled democratic governability in Uruguay. In addition, an analysis of the relation between the party and the electoral systems will be further developed in order to understand the consequences of fractionalization in the political system.